Endogone, one of the oldest plant‐associated fungi, host unique Mollicutes‐related endobacteria. Issue 4 (23rd October 2014) - Desirò, Alessandro; Faccio, Antonella; Kaech, Andres; Bidartondo, Martin I.; Bonfante, Paola
Summary: Glomeromycota have been considered the most ancient group of fungi capable of positively interacting with plants for many years. Recently, other basal fungi, the Endogone Mucoromycotina fungi, have been identified as novel plant symbionts, challenging the paradigm of Glomeromycota as the unique ancestral symbionts of land plants. Glomeromycota are known to host endobacteria and recent evidences show that also some Mucoromycotina contain endobacteria. In order to examine similarities between basal groups of plant‐associated fungi, we tested whether Endogone contained endobacteria. Twenty‐nine Endogone were investigated in order to identify Mollicutes‐related endobacteria (Mre). Fruiting bodies were processed for transmission electron microscopy and molecularly investigated using fungal and Mre‐specific primers. We demonstrate that Mre are present inside 13 out of 29 Endogone : endobacteria are directly embedded in the fungal cytoplasm and their 16S rDNA sequences cluster together with the ones retrieved from Glomeromycota, forming, however, a separate new clade. Our findings provide new insights on the evolutionary relations between Glomeromycota, Mucoromycotina and endobacteria, raising new questions on the role of these still enigmatic microbes in the ecology, evolution and diversification of their fungal hosts during the history of plant–fungal symbiosis.